2013
DOI: 10.1177/0300985813490757
|View full text |Cite
|
Sign up to set email alerts
|

Digital Squamous Cell Carcinoma in Dogs

Abstract: Squamous cell carcinoma represents 47.4% of all malignant canine digital lesions, but despite its frequency, there are few published studies available. Pathology submission records of 154 cases and follow-up of 49 animals were analyzed. On the 49 cases, histological evaluation was performed of the differentiation degree, mitotic index, presence of emboli, and immunohistochemical expression of vimentin and E-cadherin. The mean (SD) age of affected animals was 10.2 (2.3) years; no sex predisposition was recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
33
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 13 publications
4
33
1
Order By: Relevance
“…Digital squamous cell carcinoma is known to have a distinct prognosis as compared to those on other skin regions [3]. Belluco et al demonstrated that canine digital squamous cell carcinoma rarely metastasized, but had a tendency for multicentric growth [3]. In the present study, all of the squamous cell carcinomas on limb extremities were solitary.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Digital squamous cell carcinoma is known to have a distinct prognosis as compared to those on other skin regions [3]. Belluco et al demonstrated that canine digital squamous cell carcinoma rarely metastasized, but had a tendency for multicentric growth [3]. In the present study, all of the squamous cell carcinomas on limb extremities were solitary.…”
Section: Discussionsupporting
confidence: 49%
“…Similarly, previous study has reported a high occurrence of squamous cell carcinoma on the digit [16]. Digital squamous cell carcinoma is known to have a distinct prognosis as compared to those on other skin regions [3]. Belluco et al demonstrated that canine digital squamous cell carcinoma rarely metastasized, but had a tendency for multicentric growth [3].…”
Section: Discussionmentioning
confidence: 93%
“…The risk allele for DSCC in dogs had >four copies of the CNV and homozygous animals were more likely to have DSCC [54]. Black-pigmented dogs are highly overrepresented for DSCC, as 92% of samples were from black-coated dogs [59]. However, there are breeds like the Flat-Coated Retrievers that have a high copy number, black hair coat, and are not predisposed to this type of tumor [59].…”
Section: Discussionmentioning
confidence: 99%
“…Black-pigmented dogs are highly overrepresented for DSCC, as 92% of samples were from black-coated dogs [59]. However, there are breeds like the Flat-Coated Retrievers that have a high copy number, black hair coat, and are not predisposed to this type of tumor [59]. It is possible that a high copy number at the KITLG CNV is another risk factor for breeds that are already more susceptible to this particular tumor type.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, given that there is no prognostic significance and often somewhat subjective assessment, many pathologists fail to characterize it. Broder's system was not included in this case since, similar to what other studies showed [11], there can be different grades of differentiation within the same tumor, making it hard when evaluating the sample. In this study, the goal was to compare two different adapted grading schemes to ascertain that there was a morphological disparity between light-and dark-colored animals with CDSCC and some kind of grading congruence between both systems.…”
Section: Discussionmentioning
confidence: 99%